Level of Students' Digital Literacy Ability Entering the New Normal Era - Makmur Solahudin; Heru Sujiarto; Achmad Mudrikah; Usep Kosasih (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
The COVID-19 pandemic has changed the pattern of human life, including the education sector. The rapid development of digital technology is very helpful in overcoming learning problems during a pandemic as well as accelerating digital transformation in the education sector, both online learning methods and the use of digital simulations as learning technology. This study aims to measure the level of digital literacy skills of students based on the characteristics of students entering the new normal era. This study uses a quantitative descriptive approach. The population is all students studying in Depok City with a sample of 410 students obtained by random sampling. The results of the study showed that the level of student digital literacy skills of 75.3% could be included in the Good category. There is no significant difference in the level of digital literacy ability based on gender and student residence, but there is a different trend based on age and year of study, where the higher the age or year of study the higher the level of digital literacy ability, and based on the source of tuition fees for scholarship recipients. Full level indicates a higher level of digital literacy ability. In conclusion, the level of digital literacy of students could be included in the Good category. There is no difference in the level of digital literacy ability based on the gender and place of residence of students, but there are different trends based on age, year of study, and source of student tuition fees.